1996
DOI: 10.1007/bf02353355
|View full text |Cite
|
Sign up to set email alerts
|

Across six nations: Stressful events in the lives of children

Abstract: A total of 1,729 children (2nd-9th grades) in South Africa, Iceland, Poland, Australia, the U.K., and the U.S.A. rated 20 events in terms of how upsetting they are. Save in Poland, the ratings were in close agreement (r, .85-.97), placing the loss of parent at the top and a new baby sibling at the bottom. In Poland, the baby's arrival led the list. Even so, what was seen as quite upsetting fell everywhere in the same two categories--experiences that threaten one's sense of security and those that occasion pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 10 publications
2
41
0
1
Order By: Relevance
“…1,2 Retrospective, record linkage, and prospective studies have found enduring psychiatric sequelae in children bereaved after a parent's death. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, little is known about the range, course, or predictors of psychiatric outcomes in bereaved offspring.…”
Section: He Death Of a Parentmentioning
confidence: 99%
“…1,2 Retrospective, record linkage, and prospective studies have found enduring psychiatric sequelae in children bereaved after a parent's death. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, little is known about the range, course, or predictors of psychiatric outcomes in bereaved offspring.…”
Section: He Death Of a Parentmentioning
confidence: 99%
“…The death of a parent is consistently rated as one of the most stressful life events that a child can experience 1,2 . In Western countries, 4% of children experience the death of a parent and approximately 1 in 20 children in the United States experience the loss of a parent before they reach 18 years of age 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 4% of US children (2.5 million) will experience the death of one of their parents by the age of 18 years, 1 an experience consistently rated as one of the most stressful life events for children 2,3 and one associated with a number of adverse psychosocial sequelae. Retrospective, record-linkage, and prospective studies all show a significant relationship between parental death and internalizing and externalizing symptoms, impaired school performance, and sexual-risk behavior in children.…”
mentioning
confidence: 99%